A lírica imanente e afetiva de Santiago Villela Marques - Falcão, Iouchabel Sarratchara de Fatima (2023)
This thesis investigates selected lyric poems in the poetic work of Santiago Villela Marques (1967-2018), a prominent artist in the literature produced in Mato Grosso-Brazil at the beginning of the 21st century, based on the “philosophy of immanence” and the “theory of affections”, concepts developed by Benedictus de Spinoza, a Dutch philosopher of the 17th century, in his work entitled Ethics (2020). The investigation is conducted using the Comparative Literature method, between Literature and Philosophy, and is done through hermeneutic-phenomenological exercises of reading the “poetic strata”, or the poetic matter perceived by intuition through the senses, according to Maria Luiza Ramos (2011). I prioritize the imagery expression of three of the component elements of Spinoza's thought system which I call the “trinity”: “God”, “body/mind”, “affection”. I endorse that both languages, in the poetic stylistic scope and philosophical definitions, flow in the framing of expression as places of knowledge of God and affective experience through the immanent notion of the divine cause of existence. The study is divided into three investigative parts. The first is devoted to the analysis and interpretation of figurative images of God and immanence; the second and third are focused on lyrical acts as an expression of affections, as sad and happy passions, respectively. I call the poet's creative dynamics “lyrical-affective poetic art”. “Lyrical” and “affective”, together almost as a pleonasm, designate Santiago’s lyrical “art program”, in which expression is the body of an “inspirational motif”, as defined by Luigi Pareyson (1997). The interpretative exercise follows through the normative and operational resources of the poems, and through the characterization of the stylistic choices that determine the “poet's spirituality” (PAREYSON, 1997). The results converge to the idea of Santiago's lyric as an expression of experiences, real or invented, that enhance existence with active and joyful knowledge when perfected.